Risk Management in the Zakat Distribution: Case Study on Productive Zakat Program in Dompet Dhuafa Yogyakarta - Hayati, Safaah Restuning; Budianto, Gizha Utami; Putri, Syah Amelia Manggala (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This research aims to analyze the implementation of risk management on productive zakat program in Dompet Dhuafa Yogyakarta. One of the productive zakat programs is Warung Beres (Clean, Tasty, and Healthy). Descriptive qualitative approach was employed as the research method. The data of this study are obtained from semi-structured interviews with staff/employees of Dompet Dhuafa in Yogyakarta branch, mustahiq (Zakat recipients) of Warung Beres program, experts/lecturers in charge of risk management of zakat institutions and secondary data obtained from scientific journals. The research shows that the implementation of risk management is run by a timeline principle such as the stages of application, monitoring and evaluation. In addition, Dompet Dhuafa also utilizes the principles of efficiency and effectiveness. With these principles, Dompet Dhuafa Yogyakarta can be categorized good and in line with the program implementation strategy in running its program of Warung Beres although it has not been fully implemented yet. Penelitian ini bertujuan untuk menganalisis penerapan manajemen risiko pada penyaluran zakat dalam program zakat produktif di Dompet Dhuafa Kota Yogyakarta. Salah satu program zakat produktif adalah Warung Beres (Bersih, Enak, dan Sehat). Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif. Data yang digunakan dalam penelitian ini adalah data primer berasal dari wawancara semi terstruktur kepada staf/karyawan Dompet Dhuafa Yogyakarta, mustahiq/penerima manfaat Program Warung Beres, Ahli/Dosen yang membidangi manajemen risiko lembaga zakat dan data sekunder berasal dari jurnal ilmiah. Hasil analisis dari penelitian ini yaitu implementasi manajemen risiko dijalankan dengan berpedoman timeline seperti tahap pengaplikasian, monitoring dan evaluasi. Selain itu Dompet Dhuafa juga menggunakan prinsip efektif dan efisien. Dengan panduan tersebut Dompet Dhuafa Yogyakarta dalam menjalankan program Warung Beres dapat dikategorikan baik dan sesuai strategi pelaksanaan program meskipun belum sepenuhnya.